Community Quality-of-Life Indicators
X, 254 p.
Keywords: This book is a compilation of cases of best work in community indicators research. The cases describe communities that have launched their own community indicators programs. Elements that are included in the descriptions are the history of the community indicators work within the target region, the planning of community indicators, the actual indicators that were selected, the data collection process, the reporting of the results, and the use of the indicators to guide community development decisions and public policy. Community planners, community indicators researchers and urban planning specialists will find this book very helpful in learning from communities that have done community indicators work and have done it well.